2022
DOI: 10.1001/jamacardio.2022.0471
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Low-Dose Triple Combination Therapy vs Usual Care With Time at Target Blood Pressure

Abstract: IMPORTANCECumulative exposure to high blood pressure (BP) is an adverse prognostic marker. Assessments of BP control over time, such as time at target, have been developed but assessments of the effects of BP-lowering interventions on such measures are lacking.OBJECTIVE To evaluate whether low-dose triple combination antihypertensive therapy was associated with greater rates of time at target compared with usual care. DESIGN, SETTING, AND PARTICIPANTSThe Triple Pill vs Usual Care Management for Patients With M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In summary, our study, in contrast to other BP metrics, found an independent and graded inverse relationship between TIR and the risks of CVD event or mortality among patients with T2DM with well-controlled and relatively low BP. Our finding suggested that future efforts to lower CVD risk among hypertensive patients should be encouraged to utilize multiple measurements of BP with aims for attaining a high TIR in both clinical practice and clinical studies [36,37]. publicly available.…”
Section: Discussionmentioning
confidence: 94%
“…In summary, our study, in contrast to other BP metrics, found an independent and graded inverse relationship between TIR and the risks of CVD event or mortality among patients with T2DM with well-controlled and relatively low BP. Our finding suggested that future efforts to lower CVD risk among hypertensive patients should be encouraged to utilize multiple measurements of BP with aims for attaining a high TIR in both clinical practice and clinical studies [36,37]. publicly available.…”
Section: Discussionmentioning
confidence: 94%
“…The Brief Report titled “Association of Low-Dose Triple Combination Therapy vs Usual Care With Time at Target Blood Pressure: A Secondary Analysis of the TRIUMPH Randomized Clinical Trial,” published on April 13, 2022, was corrected to fix a typographical error in the Abstract Results section. In the sentence, “Those receiving the triple pill achieved a consistently higher time at target at all follow-up periods compared with those receiving usual care (mean [SD]: 0-6 weeks, 36.3% [30.9%] vs 21.7% [28.9%]; P < .001; 6-12 weeks, 5.2% [31.9%] vs 33.7% [33.0%]; P < .001; 12-24 weeks, 66.0% [31.1%] vs 43.5% [34.3%]; P < .001),” 5.2% was corrected to 55.2%.…”
mentioning
confidence: 99%